2011
DOI: 10.3855/jidc.1731
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of transfusion-transmissible infections among voluntary blood donors in South India

Abstract: This item has no abstract. Follow the link below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
2
3
1
Order By: Relevance
“…Seroprevalence of HIV was found out to be 0.13%, which is in concordance with Mythreyee et al, [23], who also reported the prevalence of HIV was 0.19%. Higher seroprevalence of 0.26%, 0.47%, 3.8% and 11.7% [3,15,27,28] have been reported by various studies.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Seroprevalence of HIV was found out to be 0.13%, which is in concordance with Mythreyee et al, [23], who also reported the prevalence of HIV was 0.19%. Higher seroprevalence of 0.26%, 0.47%, 3.8% and 11.7% [3,15,27,28] have been reported by various studies.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, previous reports from the western, eastern, and northern states of India revealed the HCV seroprevalence to be 0.29% [15], 0.35% [25], 1.5% [26], respectively. Lower prevalence of HCV was reported from Southern India by Mythreyee et al (0.22%) as well as Ather Fatima et al, (0.01%) [21,23]. Seroprevalence of HCV was relatively high in our study (0.56%) when compared with the reported rates in other parts of country.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…It is noteworthy that the molecular diagnosis techniques has been widely applied for blood screening in early 2015 in Shiyan City. Compared with the seroprevalence of HBV infections from developing countries including Mexico [ 20 ], Nepal [ 21 ], South India [ 22 ], and some African countries including Ethiopia [ 11 ], Nigeria [ 23 ], and Mali [ 24 ], HBV harbors the intermediate level. In view of age distribution, notably increased in HBV seroprevalence was found in the 36–45 and ≥45 years groups and this is similar to previous reports in Xi’an [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The selection, enrollment and assessment of HIV status of the blood donor were performed according to NACO guidelines on "Standards for Blood Banks and Blood Transfusion Services". 8,9 During the study period of 6 years, we enrolled a total of 50,043 participants in our ICTC and 12,085 voluntary blood donors in our blood bank. Among them 3282 (6.6%) and 22 (0.18%) were found to be positive for HIV infection in ICTC and blood bank, respectively.…”
mentioning
confidence: 99%